Respuesta :
OK either the equation is [tex] \sqrt{} 2x+4 - \sqrt{x} -2 =0 [/tex] or [tex] \sqrt{} 2x+4 = \sqrt{x} -2[/tex] Either way it ends up the same because if it is the first equation, I would move the [tex] \sqrt{x} - 2 [/tex] to the other side of the equation. It would become [tex] \sqrt{x} + 2[/tex].
For my example, I am going with [tex] \sqrt{} 2x+4 = \sqrt{x} -2[/tex]
Square both sides
2x+4=[tex] (x+2)^{2} [/tex]
Then use FOIL to solve the right side
2x+4=[tex] x^{2} +2x+2x+4[/tex]
Then combine like terms
2x+4=[tex] x^{2} +4x+4[/tex]
Set it equal to 0 and combine like terms
[tex]0= x^{2} -2x[/tex]
0=x(x-2)
So x=0 and x=2
If it was the other was it would be x=-2
Hope that helps.
For my example, I am going with [tex] \sqrt{} 2x+4 = \sqrt{x} -2[/tex]
Square both sides
2x+4=[tex] (x+2)^{2} [/tex]
Then use FOIL to solve the right side
2x+4=[tex] x^{2} +2x+2x+4[/tex]
Then combine like terms
2x+4=[tex] x^{2} +4x+4[/tex]
Set it equal to 0 and combine like terms
[tex]0= x^{2} -2x[/tex]
0=x(x-2)
So x=0 and x=2
If it was the other was it would be x=-2
Hope that helps.